Recent advances in developing small-molecule inhibitors against SARS-CoV-2 - Rong Xiang; Zhengsen Yu; Yang Wang; Lili Wang; Shanshan Huo; Yanbai Li; Ruiying Liang; Qinghong Hao; Tianlei Ying; Yaning Gao; Fei Yu; Shibo Jiang (Elsevier, 2022)
The COVID-19 pandemic caused by the novel SARS-CoV-2 virus has caused havoc across the entire world. Even though several COVID-19 vaccines are currently in distribution worldwide, with others in the pipeline, treatment modalities lag behind. Accordingly, researchers have been working hard to understand the nature of the virus, its mutant strains, and the pathogenesis of the disease in order to uncover possible drug targets and effective therapeutic agents. As the research continues, we now know the genome structure, epidemiological and clinical features, and pathogenic mechanism of SARS-CoV-2. Here, we summarized the potential therapeutic targets involved in the life cycle of the virus. On the basis of these targets, small-molecule prophylactic and therapeutic agents have been or are being developed for prevention and treatment of SARS-CoV-2 infection.